বিএনপি : সময়-অসময় - আহমদ, মহিউদ্দিন, ১৯৫২- (ঢাকা : প্রথমা প্রকাশনা, 2016)
Articles on Bangladesh Nationalist Party, one of the two major contemporary political parties of Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ৩৪৩-৩৬৫) ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bangladesh Nationalist Party; Bangladesh -- Politics and government -- 1971-